A general one-sided compactness result for interpolation of bilinear operators - da Silva, Eduardo Brandani; Fernandez, Dicesar Lass (MATHEMATICA SCANDINAVICA, 2019)
The behavior of bilinear operators acting on the interpolation of Banach spaces in relation to compactness is analyzed, and an one-sided compactness theorem is obtained for bilinear operators interpolated by the ρ interpolation method.